(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
INTRODUCTION Neonatal life involves the readaptation of gas exchange from the intrauterine to extrauterine environment. Stridor in this period reflects a critical airway obstruction which may have been anticipated or wholly unexpected. Many congenital and acquired diseases may cause airway obstruction and respiratory distress in infants. AIMS AND OBJECTIVES • To study the causes of stridor in neonates and infants. • Early diagnosis and treatment of the stridor to prevent morbidity and mortality. METHODS The study was observational study. In this study both qualitative and quantitative approaches were used to collect, analyse and interpret the data. Patients with stridor under age of 1 year who were referred to our department were taken in this study BY DIRECT LARYNGOSCOPY Direct laryngoscopy with macintosh laryngoscope or miller’s blade was done. Results: In our study the most common symptom at presentation was stridor which was present in all 25 cases we have taken. 13 cases were presented with difficulty in feeding along with the stridor. This was 2nd most common symptom of presentation. Stridor was associated with fever and cough cold in 13 cases. Change of cry along with stridor observed in 6 cases Result and CONCLUSION FNPL is gold standard for diagnosis and very useful and safe procedure. Use of better technology and continuous monitoring in NICU/PICU in tertiary care hospital and observation by team of doctors (Pediatrician, ENT Specialist, intensivist etc.) have definitely reduced the rate of morbidity and mortality.